Dibalik Di Balik Prestasi Atlet Penyandang Disabilitas Mental, SOIna DKI Jakarta Menjelajahi Pola Pengasuhan Orang Tua Atlet. - Purwaningsih, Lili; Deasyanti, Deasyanti; Juriana, Juriana; Gumelar, Gumgum (Jurnal Sporta Saintika, 2026)
Parenting plays a crucial role in influencing the sports participation of athletes with intellectual disabilities. Special Olympics Indonesia (SOIna) is an organization that fosters and develops the sporting potential of individuals with intellectual disabilities in Indonesia. This study aims to identify the parenting styles of athletes' parents in various sports under the auspices of SOIna. The method used was descriptive quantitative, involving 182 parents from various sports. Data collection was conducted using the PSDQ-SF questionnaire, which measures three dimensions of parenting: democratic, authoritarian, and permissive. Validity test results showed a range of values ​​​​of 0.152–0.681, while Cronbach's Alpha reliability showed a high value for democratic parenting (0.850), followed by authoritarian (0.738) and permissive (0.466). Data analysis was conducted using descriptive univariate analysis to determine the distribution of dominant parenting styles. The results showed that the majority of parents used democratic parenting (98%), while only 2% used permissive parenting, and none used authoritarian parenting. These findings indicate that a democratic approach is the primary choice in supporting the development and sports participation of athletes with intellectual disabilities, and is an important reference for the development of coaching programs and further research.